Consumer Purchasing Habits of Florida Environmental Horticulture Products - Loretta N. Satterthwaite; John J. Haydu (EDIS)
A garden center exit survey examining consumers' purchasing habits of environmental horticulture products was conducted in Florida in 2002. Nine hundred and ten surveys were completed with required information on why a particular store was chosen for shopping, availability of planned purchase items, and whether or not the final purchase matched the intentions of the buyer. The category of convenience/location was the major reason for shopping at a particular store. Other categories included price, quality, service, information, and other. This is EDIS document FE473, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, IFAS, University of Florida, Gainesville, FL. Published March 2004.